The triumph of the middle classes : - Morazé, Charles (Weidenfeld and Nicolson, 1966)
The present book is simply an attempt to understand it , and it is mean for those who wish to do the same. The writer does not sit in judgement on the dead; his sympathies, on the contrary, are warm and human. The study of the past is not sad but salutary. The middle classes of nineteenth-century Europe conquered the world not because they were middle class or European, but because the were more capable than their predecessors, or than leaders in other parts of the world, of exploiting the technical weapons put into men's hands by the progress of science. For a century and a half, science and progress calimed the European middle classes. Science and progress choose those who serve them best,...